Aplikasi Mobile Media Pembelajaran Dasar Algoritma dan Pemrograman Berbasis Android - Yusuf Ramadhan Nasution; Mhd Furqan (Universitas Dharmawangsa, 2020)
This research is a type of development research. The product development model adopts a software development model consisting of (1) Analysis of software requirements, (2) design, (3) writing code and (4) testing. Data collection techniques are done by observation, interviews and questionnaires. The testing phase is carried out with product validation by experts, testing on the first user (lecturer) and testing on the end user (student).Keywords : Learning Media, Mobile Applications, Algorithms and Programming.